2021
DOI: 10.1016/j.gerinurse.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Dementia as a mortality predictor among older adults with COVID-19: A systematic review and meta-analysis of observational study

Abstract: The purpose of this study was to systematically examine the association between dementia and mortality among older adults with COVID-19. To do so, we conducted a search of 7 databases for relevant full-text articles. A cohort study and case-control study were included. A meta-analysis was performed to synthesize the pooled odds ratio with a random-effects model. We identified studies that reported mortality among older adults with dementia and non-dementia who have COVID-19. The pooled mortality rates of demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 44 publications
3
40
0
1
Order By: Relevance
“…However, patients with Dementia are immunocompromised and may present with non-respiratory symptoms such as delirium or isolated functional decline. These situations may reduce early disease recognition and increase patients’ mortality ( Azarpazhooh et al, 2020 ; Saragih et al, 2021 ). In addition, the current review found that dyspnoea was associated with the mortality of older people with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with Dementia are immunocompromised and may present with non-respiratory symptoms such as delirium or isolated functional decline. These situations may reduce early disease recognition and increase patients’ mortality ( Azarpazhooh et al, 2020 ; Saragih et al, 2021 ). In addition, the current review found that dyspnoea was associated with the mortality of older people with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia was found to be one of the strongest risk factors for COVID-19 and associated with a higher mortality [ 126 , 127 , 128 , 129 , 130 ]. Apparently, patients with dementia have difficulties in following hygiene rules, mask requirements, behavioral instructions and distancing rules due to cognitive deficits [ 124 , 131 ].…”
Section: Chaptermentioning
confidence: 99%
“…From a health perspective, people with dementia have a high risk of contracting COVID-19 and, if infected, have a high risk of disease-related morbidity and mortality [3][4][5]. To protect those most vulnerable, governments put in place restrictions such as social distancing, isolation, and limitations on household mixing to help curb the spread of the virus [6,7].…”
Section: Introductionmentioning
confidence: 99%